HBV genotypes at the Groote Schuur Hospital Liver Clinic, Cape Town : genotype and subgenotype prevalence and the influence of ethnicity on treatment outcomes during long term clinical follow-up of patience with chronic HBV infection. - Nderu, Michelle W (Department of Medicine, 2024)
In the developing world, hepatitis B virus (HBV) is an important cause of acute and chronic liver disease. Two billion people worldwide are infected with the virus and an estimated 350 million who have failed to clear the virus have chronic infection. In Africa, HBV is endemic with 98% of the inhabitants being infected with the virus at some point in their lives. Of these 10% fail to clear the virus. The emergence of HBV-HIV coinfected cases in sub-Saharan Africa adds a new dimension in the management of this disease and highlights the need to understand the pathogenesis and treatment of HBV. HBV genotype A and D have been shown to be present in southern Africa with genotype A generally being the predominant genotype documented in South Africa. This is based on studies carried out in the Gauteng and Kwa-Zulu Natal regions. There is very little prevalence data from the W estem Cape and other provinces and there is no data on the pre-dominant HBV genotype seen in this region. This study investigates the predominant HBV genotype and subgenotypes seen at the Groote Schuur Liver Clinic, Cape Town and the possible correlations between the HBV genotype, race and disease severity. In addition early work investigating the possible presence of lamivudine resistant strains in lamivudine na'ive patients are reported. This is important as the increase in incidence of lamivudine use in HBV-HIV co-infected patients may have potential implications in lamivudine treatment management programmes. 169 chronic HBV patients from all races and age groups were recruited into the study. The HBV DNA levels, HBeAg and HBsAg status were determined as part of their standard management at the Liver Clinic. Two methods were used in combination to identify the HBV genotype of the patient using the conserved S-gene on the HBV genome. The detection of lamivudine resistant mutations on the YMDD motif was determined using nucleotide sequence analysis. The possible correlations between race, HBV genotype, interferon-a (IFN-a) treatment, virological and biochemical parameters were analysed. In this study, 73% of the patients were identified as genotype D, 27% as genotype A with one patient being genotype B2. The subgenotypes D3 and D4 were also identified in the xiii cohort. Although genotype D predominates in the Mixed race this did not reach statistical significance in this study. The genotype B2 patient was an immigrant from Taiwan, in keeping with published data from Asia. The Caucasians were older compared to the other races while the non-Caucasoids presented at an older age and with more severe disease. The Asians showed the best response to IFN-a treatment while the Black Africans had significantly lower ALB levels at presentation compared to the other races. As noted in published literature, high ALT and low HBV DNA levels correlated with a better response to IFN-a treatment. No lamivudine resistant strains were found in the lamivudine nai"ve patients but one YVDD mutation was found in a patient who was on lamivudine therapy. This study shows that genotype D and its subgenotype, D3, is the predominant genotype seen in this urban clinical cohort of patients. The unexpected presence of subgenotype D4 is documented. This interesting observation may be explained by the historically well documented population migration from the Indian and Asian Pacific islands into the Cape Town region. No lamivudine resistant strains present with in the lamivudine nai"ve patients in the clinic indicates that these strains are not yet circulating as there have been reports of the presence of these resistant strains in lamivudine nai"ve patients in South Africa. Gene polymorphisms and socio-economic factors may explain the racial difference with respect to age at HBV diagnosis. The success of IFN-a treatment may be related to the varied genetics of the population.